EFFECT OF LEADERSHIP, EFFECTIVE COMMUNICATION AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE PT. KAYAN PLANTATION, BULUNGAN DISTRICT - Juari Merilinda Santi Lenggang; Kusuma Chandra Kirana (STKIP Singkawang, 2023)
The Influence of Leadership, Effective Communication and Physical Work Environment on Employee Performance at PT. Kayan Plantation, Bulungan Regency. The research was done on purpose to help determining the influence of leadership roles, effective physical and communication work environment on performance of employee at PT. rich plantation. This reasearch type is using quantitative descriptive research. The population used was the employees of PT Kayan Plantation, Bulungan Regency. The method used in data collection used by researchers is probability sampling, ie data collection or retrieval is not randomly getting chosen, this study also uses saturated sampling or census. The sample taken for were employees of PT Kayan Plantation, Bulungan Regency. Researchers took a sample of 66 employees from PT Kayan Plantation, Bulungan Regency. Then the data is going to be tested for its quality applying the test of validity and the test of reliability. The data were then getting tested by the classical multiple regression assumption. This obtained test of normality, the test of multicollinearity and also the test of heteroscedasticity. The data were going to be analyzed by applying the determination coefficient test, partial test (t) and also simultaneous test (f). The study results found that there are the influence of leadership, effective communication and also environment of physical work on the performance of employee at PT. Kayan Plantation, Bulungan Regency. Leadership gives such a positive and significant influence on employee performance at PT. Kayan Plantation, Bulungan Regency. Effective Communication gives insignificant and negative influence on Performance of Employee at PT. Kayan Plantation, Bulungan Regency. Physical Work Environment gives positive and also significant effect on Performance of Employee at PT. Kayan Plantation, Bulungan Regency